(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
Over the last three decades, the internationalization of higher education has emerged as a focal point in the advancement of educational systems in Uzbekistan. Recognized as a predominant strategy for the enhancement of higher education, internationalization has also become a pivotal element contributing to the development of the national economy and fostering mechanisms for cultural diversity within the national education system. This paper presents a comprehensive overview of the processes involved in the internationalization of higher education in Uzbekistan within the framework of ongoing reforms in the higher education sector. Specifically, it delves into the role played by the internationalization of higher education in Uzbekistan, aiming to shed light on the historical progression of this phenomenon, its current status, and the underlying motivations driving the internationalization efforts in the country.